TREE AND SHRUB DIVERSITY IN AGROFORESTRY HOMEGARDENS IN RURAL COMMUNITY IN EASTERN AMAZON - Garcia, Bruna Naiara Rocha; Vieira, Thiago Almeida; Oliveira, Francisco de Assis (Floresta, 2017)
This article described and analyzed the tree and shrub species composition of homegardens in a rural community in Eastern Amazon, Brazil. Data were collected from 30 homegardens stratified into two groups of 15: homegardens of northeastern and homegardens of peasants from South Brazil, based on floristic surveys of 100% of the tree and shrub components. We studied the floristic composition and the preference value index (PVI), and classified the homegardens by cluster analysis. In the evaluated homegardens, 2270 vegetable plants of 67 species, 53 genera and 28 botanical families were recorded. The most representative families, according to the number of species, were Arecaceae, Rutaceae, Myrtaceae, Annonaceae, and Caesalpiniaceae. Cocos nucifera (coconut) had the highest PVI (97.37), followed by banana, orange, peach palm and avocado, confirming the preference for fruit species with commercial value. The floristic composition of homegardens revealed that coconut is the most commonly cultivated species. The species diversity in the homegardens was moderate, and evenness was considered medium, despite the dominance of species such as banana and açaí palm. The origin of the farmers did not influence the similarity among homegardens, but it influenced vegetal species richness, diversity and density, which were higher in the southerners’ homegardens. Keywords: floristic composition; family agriculture; agroforestry diversity. Resumo Biodiversidade de espécies arbóreas e arbustivas em quintais agroflorestais em comunidade rural na Amazônia Oriental: Este artigo descreveu e analisou a composição florística dos estratos arbóreos e arbustivos de quintais agroflorestais de uma comunidade rural na Amazônia Oriental, Brasil. Os dados foram coletados a partir de 30 quintais, estratificados em dois grupos de 15: quintais manejados por agricultores provenientes do nordeste brasileiro e por oriundos da região Sul do Brasil, com base em levantamentos florísticos de 100% dos componentes de árvores e arbustos. Estudou-se a composição florística e o índice de preferência valor (IVP), e classificou-se os quintais por meio de análise de cluster. Nos quintais avaliados, foram registrados 2270 indivíduos pertencentes a 67 espécies, 53 gêneros e 28 famílias botânicas. As famílias mais representativas, de acordo com o número de espécies, foram: Arecaceae, Rutaceae, Myrtaceae, Annonaceae e Caesalpiniaceae. Cocos nucifera (coco) teve o maior IVP (97,37), seguido pela banana, laranja, pupunha e abacate, indicando preferência por espécies de frutas com valor comercial. A composição florística revelou que o coco é a espécie mais cultivada. A diversidade de espécies nos quintais foi moderada, e a riqueza, considerada média, apesar da dominância de espécies, como banana e açaí. A origem dos agricultores não influenciou na semelhança entre quintais, mas influenciou na riqueza, densidade e diversidade de espécies vegetais, sendo maiores nos quintais manejados por agricultores oriundos da região sul do Brasil. Palavras-chave: composição florística; agricultura familiar; diversidade agroflorestal.